Engaging Church Leaders in a Health Needs Assessment Process to Design a Multilevel Health Promotion Intervention in Low-resource Rural Jamaican Faith Communities - Jannette Berkley-Patton; Carole Bowe Thompson; Sheila Lister; Winston Hudson; George Hudson; Elpagnier Hudson (Journal of Participatory Research Methods, 2020)
Diabetes and cardiovascular diseases (CVD) are major Jamaican public health issues. Churches may be untapped settings to extend reach and impact of diabetes and CVD prevention programs, particularly in low-resourced, rural Jamaican areas. We engaged the Jamaican Lifestyles Health Ministry Association Community Action Board in designing and conducting a health needs assessment (HNA) process to identify health conditions, priority health concerns, and potentially relevant intervention strategies to address concerns with their church-community members in rural areas. Findings from the HNA process (survey and community forum) were used by faith leaders to guide the design of a culturally-religiously tailored, multilevel diabetes/CVD risk reduction intervention, Project Faith Influencing Transformation (FIT)-Jamaica (JA). Use of HNA and collaborative intervention design processes were key to successfully completing the design of a faith-based health promotion intervention in JA churches in a timely manner.